THE EFFECT OF THE APPLICATION OF CULTURALLY RESPONSIVE TEACHING ON LEARNING INTEREST AND ABILITY TO WRITE NARRATIVE TEXTS IN INDONESIAN LANGUAGE LEARNING FOR GRADE IV STUDENTS OF UPT SDN 21 BANGKALA, JENEPONTO REGENCY - Jusmaeni, Jusmaeni; M. Agus; Andi Adam (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the effect of the application of Culturally Responsive Teaching (CRT) on the learning interest and ability to write narrative texts of grade IV students of UPT SDN 21 Bangkala, Jeneponto Regency. The research background is based on the needs of Indonesian learning that is closer to the students' local cultural experiences so that learning becomes meaningful and relevant. This study uses a quantitative approach with a quasi-experiment design of the non-equivalent control group design that involves two groups, namely the experimental group that received CRT treatment and the control group that used conventional learning. The research instruments included learning interest questionnaires, narrative text writing tests, observation sheets, and documentation. The results showed a significant difference between the two groups after the treatment was given. The average post-test score of the experimental group's writing ability reached 82.14, a significant increase from the pre-test score of 58.71. Meanwhile, the control group only increased from 57.42 to 69.28. The learning interest of students in the experimental group also increased from 62% to 86%, much higher than the control group which only increased from 60% to 71%. The t-test showed a significance value of < 0.05 on both variables, which means that CRT had a significant effect on students' learning interest and narrative text writing ability. Normalized gain analysis corroborated these findings, where the experimental group was in the high improvement category. Overall, this study emphasizes that the integration of local cultural elements through the CRT approach is able to increase student participation, motivation, and academic performance, especially in writing narrative texts. The results of this study imply that CRT is feasible as an alternative to Indonesian learning strategies that are more communicative, contextual, and in favor of the cultural diversity of students